Restructuring The Company’s Financial Performance Through Corporate Actions of Construction Sector BUMN Companies In 2017-2023 - Muhammad Daffa Naufal; Arda Raditiya Tantra; Fitri Dwi Jayanti (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyse the effect of financial performance of BUMN Construction on firm value before and after merging. This study uses moderating variables, namely mergers as a restructuring step with the aim of knowing whether mergers have an impact on strengthening or weakening the effect of financial performance on firm value. This research uses quantitative methods with a sample of 7 BUMN companies in the construction sector. Data analysis techniques using Eviews12 with panel data regression and MRA testing. The results show that financial performance 1) ROA has a positive but insignificant effect on firm value, 2) CR has a positive and significant effect on firm value, 3) DER has a negative and insignificant effect on firm value, 4) TATO has a positive and significant effect on firm value, 5) Company Size has a positive and significant effect on firm value, 6) Merger is able to moderate the effect of ROA on firm value, 7) Merger is able to moderate the effect of CR on firm value, 8) Merger is not able to moderate the effect of DER on firm value, 9) Merger is able to moderate the effect of TATO on firm value, 10) Merger is able to moderate the effect of Company Size on firm value. The conclusion in this study is that the overall impact of the Merger is able to strengthen financial performance on firm value.